Gluten-free meals in public catering - Bioletti, L.; Ferrero, B. M.; Magistroni, P.; Teriaca, M. J.; Ropolo, S.; Emma, L.; Leggio, K.; Fransos, L.; Marzullo, A.; Strumia, C.; Vietti, F.; Paltrinieri, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The Piedmont Region, the Food Hygiene and Nutrition Services of the Local Healthcare Authorities of the Piedmont Region (coordinated by ASL TO 3), and the Italian Coeliac Association Piedmont Onlus, have created a theoretical-practical training pathway for Food Business Operators to ensure a safe gluten-free meal. Study design. The aim of the study is to perform a retrospective analysis of the data collected in order to assess whether the Food Business Operators will be able to manage in the short, medium and long term audits (3-month audits, 6-month audits and 1-year audits) all the production stages of a gluten-free meal (storage, production, Methods. We have analysed the check-list used for assessing the gluten free meal, recorded from 2010 to 2016 by the staff of the Food Hygiene and Nutrition Services. They were filled out during three educational audits and they refer to 81 facilities. Results. Two-hundred and forty-three audits were conducted (3 per facility). During all stages of production of gluten-free meals (short, medium and long term), non-compliant aspects had decreased (not statistically significant). The data analysis showed a slight increase in non-compliant aspects after a 1-year storage, the trend of non-compliant aspects slightly decreased during the three production stages, the service stage registered a slight upward trend, and finally, during the basic requirements stage and control plan stage, non-compliant aspects were in sharp decline (statistically significant). Conclusions. The decrease of non-compliance guarantees safety and protection of the celiac subject, even if storage and services must be monitored more carefully in the medium term.